Classical Approach for the Fusion Reaction of Deuterium-Tritium Using 2-D Velocity Verlet Method - Dani Irawan; Sparisoma Viridi; RIzal Kurniadi; Abdul Waris (Indonesian Journal of Physics, 2015)
Fusion reaction simulation of two types of nucleon: proton and neutron, is reported in this paper. The interactions between these nucleons are assumed to be only the nuclear force and electrostatic. The modeling is done in a classical approach where molecules formed by the nucleons are being collided with each other. In the model, some parameters were configured to see how these parameters affect the simulation. Some interesting results is that we can find a stable Helium-5 and a neutron-neutron pair as the product of the collision which should not have been possible due to the the quark interactions inside them. This leads us to a conclusion that we need to add a force-model for quark interaction. We do this by using an electrostatic-like force. However using this model, we may end up to instability of the tritium. In this paper we also report a configuration where the neutron-pair is unstable while tritium is stable.